2000
DOI: 10.1046/j.1523-1755.2000.00287.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of waiting time on renal transplant outcome

Abstract: Longer waiting times on dialysis negatively impact on post-transplant graft and patient survival. These data strongly support the hypothesis that patients who reach end-stage renal disease should receive a renal transplant as early as possible in order to enhance their chances of long-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

26
366
4
7

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 587 publications
(403 citation statements)
references
References 27 publications
26
366
4
7
Order By: Relevance
“…However, after adjusting for donor and recipient demographic differences in a multivariate analysis, we found that only the age of the recipient and donor remained as significant factors that affected graft and patient survival rates (7). The recipient race, prior failed transplants, the time spent waiting on dialysis, the cold ischemia time, the retransplant rate, and HLA mismatch, all of which are known to affect the outcome of cadaver kidney transplants in general (8)(9)(10)(11) had no significant effect on graft and patient survival rates among diabetic patients included in this study. Although the incidence of rejection treatment before discharge was higher among SPK (15% versus 9%) than CRT recipients, the difference may be due in part to the longer hospitalization noted for SPK recipients.…”
Section: Discussionmentioning
confidence: 98%
“…However, after adjusting for donor and recipient demographic differences in a multivariate analysis, we found that only the age of the recipient and donor remained as significant factors that affected graft and patient survival rates (7). The recipient race, prior failed transplants, the time spent waiting on dialysis, the cold ischemia time, the retransplant rate, and HLA mismatch, all of which are known to affect the outcome of cadaver kidney transplants in general (8)(9)(10)(11) had no significant effect on graft and patient survival rates among diabetic patients included in this study. Although the incidence of rejection treatment before discharge was higher among SPK (15% versus 9%) than CRT recipients, the difference may be due in part to the longer hospitalization noted for SPK recipients.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, prolonged dialysis before transplant appears to have a detrimental effect on post-transplant outcomes (17)(18)(19). Goldfarb-Rumyantzev et al (17) found a 25% to 46% increase in graft failure for those transplanted after 6 mo to 5 yr of end stage kidney disease and 32% greater risk of death overall for those transplanted after 3 yr of end stage kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…Despite many remarkable advances during the past three decades, with transplantation now viewed unequivocally as offering the best survival and quality of life for candidates across all demographic groups, current practice remains that described by Rennie (2). Notwithstanding strong evidence that transplantation is most successful when implemented before onset of long-term dialysis, only 2.5% of patients with end-stage renal disease undergo transplantation as initial RRT (3)(4)(5).…”
mentioning
confidence: 99%